2020
DOI: 10.1002/art.41171
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of the Fibromyalgia Phenotype Varies by Age

Abstract: Objective. Many studies suggest a strong familial component to fibromyalgia (FM). However, those studies have nearly all been confined to individuals with primary FM, i.e., FM without any other accompanying disorder. The current 2011 and 2016 criteria for diagnosing FM construct a score using a combination of the number of painful body sites and the severity of somatic symptoms (FM score). This study was undertaken to estimate the genetic heritability of the FM score across sex and age groups to identify subgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Several studies have suggested that FM has a familial component. Using genome-wide association studies (GWAS) data, Dutta et al (28) investigated the genetic heritability of a continuous measure of FM severity, the FM score, calculated by summing the WPI and SSS. The study demonstrated that younger individuals (≤50 years) appear to have a much stronger genetic component to the FM score than older individuals, who were more likely to have autoimmune or structural causes of pain.…”
Section: Genetic Aspectsmentioning
confidence: 99%
“…Several studies have suggested that FM has a familial component. Using genome-wide association studies (GWAS) data, Dutta et al (28) investigated the genetic heritability of a continuous measure of FM severity, the FM score, calculated by summing the WPI and SSS. The study demonstrated that younger individuals (≤50 years) appear to have a much stronger genetic component to the FM score than older individuals, who were more likely to have autoimmune or structural causes of pain.…”
Section: Genetic Aspectsmentioning
confidence: 99%
“…Genetic factors modulate activity in relevant neurobiological systems, such as stress-response systems [ 75 , 76 , 77 ]. Further understanding of the relationship of genetic factors to fibromyalgia phenotypes, such as early onset fibromyalgia, may allow for different management strategies in different subsets [ 78 ].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Several studies suggest a familial/genetic predisposition for FSD. Moderate levels of heritability were found in twin studies of FM (Dutta et al, 2020), IBS (Svedberg, Johansson, Wallander, & Pedersen, 2008), and CFS (Buchwald et al, 2001). Which particular genes are responsible remains unknown as genome-wide association studies of FSD are in early stages, with limited power and/or shallow phenotyping (Bonfiglio et al, 2018;Docampo et al, 2014;Schlauch et al, 2016).…”
mentioning
confidence: 99%